Immature platelet fraction and the extent of coronary artery disease: A single centre study. (May 2017) - Verdoia, Monica; Nardin, Matteo; Rolla, Roberta; Marino, Paolo; Bellomo, Giorgio; Suryapranata, Harry; De Luca, Giuseppe; ,
Abstract: Background and aims: Immature platelet fraction (IPF) represents the quote of younger and larger sized circulating platelets, a potential marker of platelet reactivity and major cardiovascular events. We aimed to assess the relationship between IPF levels and the prevalence and extent of coronary artery disease (CAD) in patients undergoing coronary angiography. Methods: A cohort of consecutive patients undergoing coronary angiography in a single centre were included. Significant CAD was defined as at least 1 vessel stenosis >50%, while severe CAD was defined as left main and/or three-vessel disease. IPF levels were measured at admission by routine blood cells count (A Sysmex XE-2100). Results: We included 1789 patients, divided according to quartiles values of IPF. IPF levels were directly related to active smoke ( p  = 0.02), and non-acute coronary syndrome as indication to angiography ( p  < 0.001), higher levels of haemoglobin and uric acid ( p  < 0.001, respectively) and lower platelet count ( p  = 0.003). Angiographic features did not significantly differ according to quartiles values of IPF, but for a lower degree of TIMI flow in patients with a higher percentage of reticulated platelets ( p  = 0.01) and a higher rate of lesions involving bifurcations ( p  = 0.05). IPF levels did not affect the prevalence of CAD (77% vs. 82.2% vs. 79.1% vs. 75.6%, p  = 0.34, adjusted OR [95% CI] = 0.93 [0.82–1.05], p  = 0.22), nor of severe left main/three-vessel CAD (28.5% vs. 34.4% vs. 32.2% vs. 33.1%, p  = 0.27; adjusted OR [95% CI] = 0.99 [0.90–1.1], p  = 0.88). Conclusions: The present study shows that among patients undergoing coronary angiography, the immature platelet fraction (IPF) is not associated with the prevalence and extent of coronary artery disease, and, therefore, should not be overlooked as a marker of coronary atherosclerosis. Highlights: Reticulated platelets (RP) have emerged as indicator of platelet reactivity and cardiovascular events. Immature platelet fraction (IPF) provide a fast estimation of the quote of circulating RPs. In 1789 patients undergoing coronary angiography, the relationship between IPF and coronary artery disease was assessed. In our population IPF levels were not associated to the prevalence and extent of CAD. Therefore RPs should not be overlooked as a marker of coronary atherosclerosis.